Melampaui Pembelajaran Konvensional: Analisis Dampak Pembelajaran Kolaboratif terhadap Keterlibatan Aktif Siswa Pendidikan Vokasi - Andini Rivanka Harahap; Angela Shakila Aurel Pane; Elisabeth Sihombing; Lihardo Manik; Nasib H. Sihombing; Sunita Manalu; Tesalonika Simanjuntak; Setia T. Sitohang; Lydia Purba (Yayasan Bayt Shufiya Nusantara, 2026)
Student learning activeness is a fundamental aspect of the learning process because it reflects students’ cognitive, affective, and psychomotor involvement. In classroom practice, many students remain passive, reluctant to participate in discussions, hesitant to ask questions, and lacking confidence to express their opinions. These conditions indicate that the learning process has not fully encouraged active student participation. Therefore, appropriate and effective teaching strategies are required to enhance student learning activeness. This study aims to conduct an in-depth analysis of teachers’ strategies in increasing student learning activeness through collaborative learning at SMK Swasta GKPI 2 Pematangsiantar. This study employs a descriptive qualitative approach, utilizing observation, interviews, and documentation as the primary data collection techniques. The results reveal that systematically designed and well-managed collaborative learning significantly improves student learning activeness. Improvements are evident in students’ participation in group discussions, confidence in asking questions, ability to express opinions, and active involvement in group work. Teacher strategies such as forming heterogeneous groups, assigning clear roles to group members, managing group discussions, and implementing process-based assessment are proven to be effective in creating active and interactive learning environments. Therefore, collaborative learning can be considered an effective instructional strategy to enhance student learning activeness in vocational high schools.